RANCANG BANGUN TRAINER TERINTEGRASI RANGKAIAN PENYEARAH GELOMBANG DAN PENGUAT OP-AMP BERBASIS MIKROKONTROLER ATMEGA 32 - Resa Pramudita; Ase Suryana (Universitas Widyatama, 2019)
Half-wave rectifier, full-wave rectifier, inverting op-amp amplifier, and non-inverting op-amp amplifier are basic electronic practicum material in each Electrical Engineering Department. During this practicum is carried out by arranging the circuit manually using breaadboard, so it requires a long time and is inefficient. In this study a trainer with integrated modules was designed. The module consists of a wave rectifier module, transistor amplifier module, op-amp amplifier module, and logic gate. This trainer is designed based on the ATmega 32 microcontroller which functions to select modules, display module workmanship, and basic logic gate programs. The method used in this research is experiment and simulation. From the test results, the half-wave rectifier and full-wave rectifier modules respond according to the simulation of ideal conditions. While the results of testing the inverting amplifier and non-inverting amplifier, show both modules can function in accordance with theory and simulation. So it can be concluded that this trainer can be used for practical learning.